Multi-omics analysis of zinc finger protein 683 as a prognostic biomarker for immune infiltration in clear cell renal cell carcinoma - Yicheng Guo; Yini Wang; Guixin Ding; Tianqi Wang; Fengze Sun; Xiaohong Ma; Jitao Wu (BMC Cancer)
Abstract Background The abnormal expression of Zinc Finger Protein 683 (ZNF683) has been implicated in various cancers, yet its role in clear cell renal cell carcinoma (ccRCC) remains underexplored. Understanding the prognostic significance of ZNF683 and its correlation with tumor-infiltrating immune cells in ccRCC could offer insights into its potential as a therapeutic target. Methods We assessed the expression of ZNF683, its correlation with clinical pathological variables, and clinical outcomes using databases such as The Cancer Genome Atlas (TCGA), Tumor Immune Estimation Resource (TIMER), UALCAN, Gene Expression Profiling Interaction Analysis (GEPIA), and Kaplan-Meier (KM) plotter. Additionally, quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) was used to evaluate ZNF683 transcriptional expression in renal cancer tissues. A comprehensive analysis of multiple databases, including TIMER, GEPIA, TISIDB, the ESTIMATE algorithm, and the CIBERSORT algorithm, was conducted to determine the correlation between ZNF683 and tumor-infiltrating immune cells in ccRCC. Results Our analysis revealed that ZNF683 mRNA levels were significantly elevated in ccRCC tissues compared to normal tissues. ZNF683 protein was highly expressed in cancer tissues, particularly in renal tumor cells, as indicated by the Human Protein Atlas (HPA). Notably, increased ZNF683 expression was significantly associated with the infiltration of CD8 + T cells, B cells, macrophages, Treg cells, NK cells, and dendritic cells in ccRCC. Bioinformatics analyses demonstrated a strong correlation between ZNF683 expression and several immune checkpoints, including PD-1. This association suggests that ZNF683 might impact the efficacy of immunotherapy in ccRCC. Patients with high ZNF683 expression exhibited reduced sensitivity to immunotherapy. Conclusions Our study identifies ZNF683 as a significant prognostic biomarker in ccRCC and highlights its correlation with immune cell infiltration. These findings suggest that ZNF683 could play a crucial role in ccRCC progression and response to immunotherapy, warranting further investigation into its potential as a therapeutic target.